Discrimination between magnetic shear and toroidal electric field effects in TJ-II plasmas - López-Bruna, D.; Romero, J. A.; Castejón, F.; Estrada, T.; Ascasíbar, E. (Вопросы атомной науки и техники, 2002)
The response of TJ-II plasmas to an induced toroidal electric field, Eǿ , was studied in past experiments with the aid of Ohmic inducted current. It was found that positive induced plasma current, Ip, degrades the confinement while negative Ip improves it. Candidates to provide a physical explanation are Eǿ itself and the plasma current via magnetic shear modification. A movable mirror in an electron Cyclotron Heating line of TJ-II permits varying the refraction index of the heating wave, N||, thus allowing for non inductive electron cyclotron current drive (ECCD) up to Ip ≈ ±1 kA. Comparing discharges without and with ECCD (changing shear but not Eǿ ) but sharing the same transformer action (changing both shear and Eǿ ), magnetic shear and electric field effects can be discriminated in time. It has been found that plasma response with ECCD is delayed respect to the transformer switch-on time, clearly pointing to shear effects. Effects related to Eǿ alone, if they exist, are weaker.